AN IMPROVED METHOD FOR TREATING THE RESIDUAL CAVITY DURING ECHINOCOCCECTOMY FROM THE LIVER WITH AN ELASTIC FIBROUS CAPSULE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
One of the urgent issues in the surgery of echinococcosis of the liver remains the option of treatment of the residual cavity, implying both antiparasitic efficacy and the possibility of accelerating the processes of obliteration of the fibrous capsule. To assess the effectiveness of the proposed method, 2 groups were formed. There were 104 patients in the main group and 117 in the comparison group. In patients with echinococcosis of the liver, the presence of an elastic fibrous capsule allows for open operations in 74.5-78.7% (for both groups) to perform complete suturing of the residual cavity (54.3-69.3%) or drainage (9.3-20.2%), in 12-12.8% of patients it is possible to perform abdominization of the residual cavity and only in 9.3-In 12.8% of cases, due to the difficult localization of the cyst (more often deeply intraparenchymatous), the operation is limited to drainage of the residual cavity with a minimum volume of pericystectomy.